ANALYSIS OF THE NEED FOR RENEWABLE ENERGY LEARNING VIDEOS BASED ON PROBLEM-BASED LEARNING (PBL) AT SMA NEGERI 5 LUBUKLINGGAU CITY - winda_15 surati (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to analyze the need for the development of renewable energy learning videos based on Problem Based Learning (PBL) at SMA Negeri 5 Lubuklinggau. The background of this study is based on the limited use of innovative learning media that can increase student engagement. The research method used is a descriptive qualitative approach through observation, interviews with teachers, and distribution of questionnaires to students. The results show that teachers and students need interactive, contextual learning videos that are suitable for the characteristics of the students. PBL-based renewable energy learning videos are considered capable of helping students understand the material more deeply through the presentation of real problems that are close to their daily lives. The conclusion of this study emphasizes the importance of developing PBL-based renewable energy learning videos as innovative and effective learning support media to improve the quality of the learning process at SMAN 5 Lubuklinggau City. Keywords: Learning Videos, Renewable Energy, Problem-Based Learning.